2018
DOI: 10.1049/iet-pel.2018.5474
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bi‐directional single‐inductor multi‐input battery system with state‐of‐charge balancing control

Abstract: This study presents a bi-directional single-inductor multi-input single-output battery system with state-of-charge (SOC) balancing controller. In the discharging operation mode of the battery system, the SOC balancing between multiple batteries is achieved by adaptively modulating the multipliers of the discharging rate of each battery cell, while maintaining the output voltage regulated at the desired value by modulating the average value of duty cycle of the power converter. The SOC balancing is achieved nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Instead, it is a combination of both systems. Table 2 shows a comparison between the presented WEDES system in this paper, conventional WPT system [18,21,22], and conventional BESS system [23][24][25]. It is shown that the presented WEDES system combines the advantages of both the conventional WPT system and BESS system, and can achieve bus voltage regulation and SOC balancing, and allow for fast and safe exchange/swapping of smaller and lighter battery modules with WPT technology.…”
Section: Additional Commentmentioning
confidence: 99%
“…Instead, it is a combination of both systems. Table 2 shows a comparison between the presented WEDES system in this paper, conventional WPT system [18,21,22], and conventional BESS system [23][24][25]. It is shown that the presented WEDES system combines the advantages of both the conventional WPT system and BESS system, and can achieve bus voltage regulation and SOC balancing, and allow for fast and safe exchange/swapping of smaller and lighter battery modules with WPT technology.…”
Section: Additional Commentmentioning
confidence: 99%
“…The parallel‐connected MICs are popular for achieving high gain without isolation requirements. Thus these find their applications in the fields of RES, smart grids, ESS, HEVs where high dc gain is the major requirement [13, 14, 17–22, 24, 25, 30, 38, 46–48, 53, 54, 56, 57, 88].…”
Section: Categorisation Of Micsmentioning
confidence: 99%
“…14 a [8]. Thereby, these modular MICs increase the reliability of the overall system which is significant in several applications like micro and nanogrids, EVs, and ESS [11–14, 16–20, 22, 24, 25, 33, 35, 38, 46, 48, 54, 57, 88]. The modularity in the source end can comfortably be extended to the load end and make the system modular on the source and load end as well.…”
Section: Categorisation Of Micsmentioning
confidence: 99%
See 1 more Smart Citation
“…The balancing is limited to only two cells and the charging speed is not optimized with operating conditions. In [5], bidirectional charging/discharging balance is adopted.…”
Section: Introductionmentioning
confidence: 99%